A food-grade layered hydrogel and preparation method thereof
By using two-way freezing molds and liquid nitrogen freezing treatment methods in food-grade hydrogels, the problems of disordered structure and insufficient mechanical properties of the existing hydrogels are solved, and layered hydrogels with high hardness and toughness are prepared to meet the chewing needs of food and simplify the preparation process.
Patent Information
- Application Number
- CN202410459264.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-04-17
AI Technical Summary
The existing hydrogel has disordered structure and weak mechanical properties, making it difficult to meet the chewing needs of food. At the same time, the preparation method is complex and the operation is difficult.
A hydrogel with a layered structure is prepared using a bidirectional freezing mold. The hydrogel with a stirring in a water bath of 60-100°C was poured into a bidirectional freezing mold for cooling and molding, and then bidirectional freezing treatment was performed in liquid nitrogen to form a hydrogel with high hardness and toughness.
The prepared hydrogel has higher horizontal hardness, which can better meet the chewing needs of food. At the same time, the preparation process is simple, the process requirements are low, and it is easy to mass production.
Smart Images

Figure CN118290827B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogel materials, and particularly relates to a food-grade layered hydrogel and a preparation method thereof. Background Art
[0002] Many natural biological tissues have a typical layered structure. Hydrogels are key materials for preparing layered tissue structures due to their good biocompatibility, biodegradability, nutritional properties and edibility. However, ordinary hydrogels have disordered structures, and natural polysaccharide hydrogels have weak mechanical properties, making it difficult to meet the chewing requirements of food.
[0003] The current methods for preparing layered hydrogels include 3D printing, ion diffusion, electromagnetic signal regulation, etc. However, they have problems such as complicated processes, difficult operations, and toxic reagents. Summary of the invention
[0004] In order to overcome the shortcomings of the related art, the present invention provides a food-grade layered hydrogel, which is an ordered layered structure with higher hardness in the horizontal direction and can better meet the chewing requirements. At the same time, its preparation process is simple, the process requirements are low, and it is convenient for actual mass production.
[0005] The technical solution adopted by the present invention to solve the technical problem is:
[0006] A food-grade layered hydrogel, which is prepared by a two-way freezing mold and has a layered structure, and its raw material components include: polysaccharides with a flexible molecular chain conformation for making the taste more elastic and polysaccharides with a rigid molecular chain conformation for enhancing the gel hardness and improving the toughness of the taste, wherein the ratio of polysaccharides with a rigid molecular chain conformation to polysaccharides with a flexible molecular chain conformation is 4:1 to 4:6;
[0007] The polysaccharide with a flexible molecular chain conformation is one or more of pectin, tamarind gum, guar gum, locust bean gum, and konjac glucomannan;
[0008] The polysaccharide having a double helix or triple helix molecular chain conformation is one or more of κ-carrageenan, xanthan gum, gellan gum, and curdlan;
[0009] The bidirectional freezing mold comprises a mold body, a wedge-shaped gasket is placed in the mold body, and the inclination angle of the wedge-shaped gasket is 15° to 30°;
[0010] The parallel direction hardness of the hydrogel is 0.15N-0.35N.
[0011] A further technical solution of the present invention is:
[0012] Furthermore, in terms of mass percentage, the total proportion of the polysaccharide with a flexible molecular chain conformation and the polysaccharide with a rigid molecular chain conformation is 0.5% to 2%, and the remainder is water.
[0013] Furthermore, the bidirectional freezing mold also includes a liquid nitrogen container, the mold body includes a lower copper column and an upper hollow cylindrical tube, the upper hollow cylindrical tube sits on the lower copper column, the wedge-shaped gasket is made of polydimethylsiloxane, and the upper hollow cylindrical tube is made of polytetrafluoroethylene.
[0014] Furthermore, the lower copper column includes a columnar base portion and a columnar connecting portion connected to the middle of the top surface of the base portion, the diameter of the connecting portion is smaller than the base portion, and the upper hollow cylindrical tube includes a cylindrical portion and an annular edge portion, the annular edge portion is connected to the bottom of the inner wall of the cylindrical portion, and the columnar connecting portion is tightly plugged into the annular edge portion.
[0015] As described above, hydrogen bonds occur between the hydrophilic colloids in the formula of the present invention to form a gel with an entangled network structure, and the double helix structure of the polysaccharide with a rigid molecular chain conformation helps to make the network structure more stable. The formed hydrogel has good biocompatibility, safety and other characteristics, meeting food grade requirements.
[0016] Accordingly, the present invention also requires adding a layered structure to the hydrogel and improving the mechanical properties to meet the needs of simulated food.
[0017] The method for preparing a food-grade layered hydrogel as described in any one of the above items comprises the following steps:
[0018] Step 1: Build a two-way freezing mold;
[0019] Step 2: Stir the hydrophilic colloid in a water bath at 60-100°C for 1-2 hours to obtain a sol for standby use;
[0020] Step 3: Pour the sol prepared in step 2 into the mold body in step 1 while it is still hot and cool it at room temperature to form it;
[0021] Step 4: Place the mold body in a liquid nitrogen container to reduce temperature loss. Pour liquid nitrogen over 3 / 5 to 4 / 5 of the copper column. Ice crystals first nucleate from the bottom of the wedge-shaped gasket close to the copper column. The growth rate of ice crystals in the vertical direction is always faster than that along the slope. The closer the wall is to the copper column, the faster it forms until the gel is completely frozen.
[0022] Step 5: Thaw at room temperature for 1.5 to 2.5 hours until the gel is thawed.
[0023] Furthermore, in step 3, the sol can submerge the wedge-shaped block but will not overflow the mold body.
[0024] Furthermore, in step 4, liquid nitrogen is poured in to cover 2 / 3 of the copper column.
[0025] Furthermore, in step 5, the mixture is thawed at room temperature for 2 hours until the gel is thawed.
[0026] Compared with the prior art, the present invention has at least the following beneficial effects:
[0027] 1. The main raw material of the present invention is hydrophilic colloid, which is widely present in the grains, fruits, roots, tubers and bulbs of plants; it has the advantages of wide sources and edible, and the prepared hydrogel is food-grade hydrogel with simple ingredients and non-toxic and harmless;
[0028] 2. The hydrogel of the present invention is prepared by a bidirectional freezing method, and has a layered structure in the horizontal direction. The hardness in the horizontal direction can reach more than 0.15N, and it is more chewable;
[0029] 3. A synergistic gel formed by polysaccharides with a rigid molecular chain conformation and polysaccharides with a flexible molecular chain conformation that form a double helix structure or a triple helix structure after self-assembly. The polysaccharides with a rigid molecular chain conformation help to improve the toughness and enhance the hardness of the gel; the polysaccharides with a flexible molecular chain conformation provide the system with an elastic taste and prolong the residence time in the oral cavity;
[0030] 4. The optimal ratio of polysaccharides with rigid molecular chain conformation: polysaccharides with flexible molecular chain conformation is 4:1 to 4:6. Within this ratio range, for systems with high xanthan gum content, the content of ordered structures between molecular chains increases, the cross-linking density increases, the rigidity of the structure increases, and the parallel hardness of the hydrogel increases; beyond this range, for weak gel systems with high konjac glucomannan content, the two-way freezing method enhances the interaction between molecules, but does not enhance the gel structure;
[0031] 5. Compared with the combination of xanthan gum and konjac glucomannan, the hardness of the hydrogel obtained by the combination of κ-carrageenan and konjac glucomannan is 0.35N, which is higher and can be used by consumers who have higher requirements for hardness;
[0032] 6. The food-grade hydrogel of the present invention is processed by a bidirectional freezing method, which has a simple preparation method, low process requirements, and is convenient for actual batch production. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 : is a scanning electron micrograph of the original gel (A) and a scanning electron micrograph of the longitudinal section (B) and the scanning electron micrograph of the cross section (C) of the hydrogel prepared in Example 1 of the present invention;
[0034] Figure 2 is the TPA test of the hydrogel prepared in Example 1 of the present invention;
[0035] Figure 3 The longitudinal section scanning electron micrograph (A) and the cross section scanning electron micrograph (B) of the hydrogel prepared in Comparative Example 1 of the present invention are shown;
[0036] Figure 4 It is a schematic diagram of the overall structure of the bidirectional freezing mold after being assembled;
[0037] Figure 5 It is a schematic structural diagram of a wedge-shaped gasket of a bidirectional freezing mold of the present invention;
[0038] Figure 6 It is a structural schematic diagram of the copper column of the bidirectional freezing mold of the present invention;
[0039] Figure 7 It is a structural schematic diagram of the hollow cylindrical tube of the bidirectional freezing mold of the present invention.
[0040] In the figure, 1 is a copper column, 11 is a connecting portion, 2 is a hollow cylindrical tube, 21 is an annular edge portion, and 3 is a wedge-shaped gasket. DETAILED DESCRIPTION
[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0042] Embodiment 1:
[0043] A method for preparing a food-grade layered hydrogel is as follows:
[0044] Step 1: Add 0.4 g of konjac glucomannan and 1.6 g of xanthan gum to 398 g of water and stir in a 90° C. water bath for 1.5 h to obtain a sol with a total solid content of 0.5% for standby use.
[0045] Step 2: Pour the sol prepared in step 1 into a two-way freezing mold while it is still hot and cool it at room temperature to form the mold at an angle of 30°.
[0046] Step 3: Place the mold in a foam box to reduce temperature loss, and pour liquid nitrogen to cover 12 / 3 of the copper column until the gel is completely frozen;
[0047] Step 4: Thaw at room temperature for two hours until the gel thaws. After thawing, cut into 3cm×3cm×1.5cm samples for subsequent performance testing.
[0048] Figure 2 This is the TPA test of the hydrogel prepared in this example. The parallel hardness of the food-grade layered hydrogel obtained by the TPA test is 0.15N. Figure 1 As shown in (A), the original gel without bidirectional freezing treatment is a long and narrow pore structure arranged axially and parallel to each other. Figure 1 As shown in (B) and (C), the hydrogel treated by bidirectional freezing of the present invention is a layered structure. Both konjac glucomannan and xanthan gum are non-gelling polysaccharides, and hydrogels can be prepared by synergistic action. Bidirectional freezing helps to produce a layered structure and improve mechanical properties.
[0049] The bidirectional freezing and thawing of the present invention is a simple and efficient method. When the mold filled with gel is slowly immersed in a liquid nitrogen bath from one end, the following steps will occur: ice crystals first nucleate from the bottom of the wedge-shaped gasket close to the copper column; ice crystals grow upward and squeeze the molecular chains on both sides to form walls. Since the silica gel material transfers temperature slowly, the growth of ice crystals in the slope direction is not completely completed; ice crystals complete the growth in the slope direction, and the ice crystals from the bottom of the wedge-shaped gasket to the top of the gel grow faster, gradually forming pore walls; the growth rate of ice crystals in the vertical direction is always faster than the growth along the slope, and the closer the part of the wall is to the copper column, the faster it forms; continue this process, the pore wall forms a special layered stack, and bidirectional freezing is completed; thereby preparing a hydrogel with a food-grade layered structure. The present invention constructs a bidirectional freezing gradient through a bidirectional freezing and thawing method to form a directional ice layer in the water of the gel.
[0050] The bidirectional freezing mold comprises a mold body, and a wedge-shaped gasket 3 is placed in the mold body.
[0051] Furthermore, the inclination angle of the wedge-shaped gasket 3 is 15° to 30°.
[0052] Furthermore, the bidirectional freezing mold also includes a liquid nitrogen container, the mold body includes a lower copper column 1 and an upper hollow cylindrical tube 2, the upper hollow cylindrical tube 2 sits on the lower copper column 1, and the wedge-shaped gasket 3 is made of polydimethylsiloxane.
[0053] Furthermore, the upper hollow cylindrical tube 2 is made of polytetrafluoroethylene.
[0054] Furthermore, the lower copper column 1 includes a columnar base portion and a columnar connecting portion 11 connected to the middle of the top surface of the base portion, the connecting portion 11 has a smaller diameter than the base portion, and the upper hollow cylindrical tube 2 includes a cylindrical portion and an annular edge portion 21, the annular edge portion 21 is connected to the bottom of the inner wall of the cylindrical portion, and the columnar connecting portion 11 is tightly plugged into the annular edge portion 21.
[0055] It should be noted that the polysaccharide with a rigid molecular chain conformation in this article specifically refers to a double helix structure or a triple helix structure formed by self-assembly of polysaccharide molecular chains through hydrogen bonding interactions or hydrophobic interactions. Polysaccharides with flexible molecular chain conformations, in contrast to polysaccharides with rigid molecular chain conformations, cannot be assembled into double helix or triple helix structures. Since the growth direction of ice crystals is basically from bottom to top, the parallel direction refers to the direction parallel to the growth direction of the ice crystals, and the vertical direction refers to the direction perpendicular to the growth direction of the ice crystals. The original gel refers to the gel that has not undergone bidirectional freezing treatment.
[0056] TPA test: The gel was cut into a cuboid of approximately 3 cm × 3 cm × 1.5 cm and tested in TPA mode on a texture analyzer equipped with a 5.0 kg sensor, and the test probe was selected as P / 0.5. The test conditions were as follows: pre-test speed was 1 mm / s, test speed was 0.5 mm / s, post-test speed was 1 mm / s, the pressing distance was 2 mm, and the trigger force was 3 g. A time of 5 seconds was allowed to pass between two compression cycles.
[0057] Embodiment 2:
[0058] The preparation steps of a food-grade lamellar hydrogel are the same as those in Example 1. On this basis, the ratio of the synergistic gel is changed to K4X6, K6X4, and K8X2 to explore the effect of the polysaccharide ratio on bidirectional freezing, wherein K refers to konjac glucomannan (KGM) and X refers to xanthan gum.
[0059] The hydrogels with food-grade layered structures obtained by TPA test all have good layered structures. The parallel direction hardness of K4X6 increases from 0.11N of the hydrogel made by ordinary circular pads to 0.2N of the hydrogel made by using wedge-shaped pads, and the parallel direction hardness of K6X4 increases from 0.10N to 0.15N. The parallel direction hardness of K8X2 is not significantly increased. Example 2 changes the ratio of hydrophilic colloids on the basis of Example 1. For systems with high xanthan gum content, the content of ordered structures between molecular chains increases, the crosslinking density is increased, the rigidity of the structure is increased, and the parallel direction hardness of the hydrogel is improved. For weak gel systems with high konjac glucomannan content, the two-way freezing method enhances the interaction between molecules, but does not enhance the gel structure. The best ratio obtained is polysaccharides with rigid molecular chain conformation: polysaccharides with flexible molecular chain conformation = 4:1 to 4:6.
[0060] Embodiment 3:
[0061] The preparation steps of a food-grade lamellar hydrogel are the same as those in Example 1, except that xanthan gum is replaced by κ-carrageenan.
[0062] The parallel hardness of the obtained food-grade lamellar hydrogel tested by TPA was 0.35 N. Example 3 The raw materials were changed on the basis of Example 1. The addition of konjac glucomannan enhanced the hydrogen bond interaction of the κ-carrageenan gel network, formed a dense network structure, and improved the parallel hardness of the hydrogel.
[0063] Embodiment 4:
[0064] The preparation steps of a food-grade layered hydrogel are the same as those in Example 1, on this basis, part of the xanthan gum is replaced by κ-carrageenan.
[0065] The parallel hardness of the obtained food-grade layered hydrogel by TPA test is 0.24 N. Example 4 uses a ternary composite material, and the compounding effect is better than that of Example 1, so that the gel has a certain chewiness and a longer presence in the mouth.
[0066] Comparative Example 1:
[0067] The preparation steps of the hydrogel are the same as those of Example 1. On this basis, the angle of the wedge-shaped mold is adjusted to 0°, and the parallel hardness of the hydrogel is tested.
[0068] The parallel hardness of the hydrogel obtained by TPA test is 0.13N, and the microstructure is as follows Figure 3 As shown, the long holes in the parallel direction are evenly arranged along the freezing direction, and the holes in the vertical direction are elliptical holes. Comparative Example 1 adjusts the angle of the wedge-shaped mold to 0° on the basis of Example 1. When the angle of the wedge-shaped mold is 0°, the temperature gradient from bottom to top will cause ice crystals to nucleate and grow in a specific direction. After thawing, the ice crystals are removed, and the hydrogel produces pores with a honeycomb structure, a non-layered structure, but the hardness in the horizontal direction is low, which cannot enhance the chewiness of the gel and is not conducive to improving the taste experience.
[0069] Comparative Example 2:
[0070] The preparation steps of the hydrogel are the same as those in Example 1. On this basis, the angle of the wedge-shaped mold is adjusted to 10°, and the parallel hardness of the hydrogel is tested.
[0071] The parallel hardness of the hydrogel obtained by TPA test is 0.13N. The wedge-shaped mold with a smaller angle makes the ice crystals grow faster, which cannot squeeze the molecular chains to produce more cross-links, and the hardness in the horizontal direction is relatively low.
[0072] Comparative Example 3:
[0073] The preparation steps of the hydrogel are the same as those in Example 1. On this basis, the angle of the wedge-shaped mold is adjusted to 60°, and the parallel hardness of the hydrogel is tested.
[0074] The parallel hardness of the hydrogel obtained by TPA test was not significantly improved. The wedge-shaped mold with a larger angle may lead to the formation of larger ice crystals or irregular ice crystal shapes. The large pores produced after thawing cannot provide support for the hydrogel.
[0075] Comparative Example 4:
[0076] The preparation steps of the hydrogel were the same as those in Example 1. On this basis, the freeze-thaw method was changed, and the gel was placed in a -15°C refrigerator for 8 hours and then thawed at room temperature for 2 hours.
[0077] The hardness of the hydrogel obtained by TPA test is 0.165N, but the hardness difference in each direction is small. The gel has an anisotropic structure after bidirectional freeze-thaw. The hardness difference in different parts of the gel will bring different taste experiences and the taste is more layered.
[0078] Comparative Example 5:
[0079] This comparative example provides a food-grade hydrogel with a layered structure. The preparation method is basically the same as that of Example 1, except that konjac glucomannan is replaced by xanthan gum of the same weight, and the rest remain unchanged, so that a gel cannot be formed.
[0080] In summary, the experiments of Examples 1-4 and Comparative Examples 1-5 illustrate the influence of the selection and proportion of hydrophilic colloids and the freeze-thaw conditions on the strength and anisotropic structure of the hydrogel, and the performance of the hydrogel can be improved by adjusting the conditions.
[0081] The above embodiments are only used to illustrate the present invention, and are not intended to limit the present invention in other forms. Those skilled in the art may modify or remodel the above technical contents into equivalent changes. Therefore, any simple modification made to the above embodiments without departing from the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a food-grade layered hydrogel, characterized in that: The steps include: Step 1: Build a two-way freezing mold; Step 2: Stir the hydrophilic colloid in a 60-100ºC water bath for 1-2 h to obtain a sol for standby use; Step 3: Pour the sol prepared in step 2 into the mold body in step 1 while it is still hot and cool it at room temperature to form it; Step 4: Place the mold body in a liquid nitrogen container to reduce temperature loss. Pour liquid nitrogen over 3 / 5 to 4 / 5 of the copper column. Ice crystals first nucleate from the bottom of the wedge-shaped gasket close to the copper column. The growth rate of ice crystals in the vertical direction is always faster than that along the slope. The closer the wall is to the copper column, the faster it forms until the gel is completely frozen. Step 5: Thaw at room temperature for 1.5-2.5 hours until the gel thaws; The hydrogel is prepared by a two-way freezing mold and has a layered structure. The raw material components include: polysaccharides with a flexible molecular chain conformation for making the mouth feel more elastic and polysaccharides with a rigid molecular chain conformation for enhancing the gel hardness and improving the toughness of the mouth feel, and the ratio of polysaccharides with a rigid molecular chain conformation to polysaccharides with a flexible molecular chain conformation is 4:1 to 4:
6. The polysaccharide with a flexible molecular chain conformation is one or more of pectin, tamarind gum, guar gum, locust bean gum, and konjac glucomannan; The polysaccharide having a rigid molecular chain conformation is at least one of κ-carrageenan and xanthan gum; The bidirectional freezing mold comprises a mold body, a wedge-shaped gasket is placed in the mold body, and the inclination angle of the wedge-shaped gasket is 15°~30º; The parallel hardness of the hydrogel is 0.15N~0.35N.
2. The method for preparing a food-grade layered hydrogel according to claim 1, characterized in that: Calculated by mass percentage, the total proportion of polysaccharides with flexible molecular chain conformation and polysaccharides with rigid molecular chain conformation is 0.5%~2%, and the rest is water.
3. The method for preparing a food-grade layered hydrogel according to claim 1, characterized in that: The wedge-shaped gasket is made of polydimethylsiloxane.
4. The method for preparing a food-grade layered hydrogel according to claim 1, characterized in that: In step 3, the sol can submerge the wedge-shaped block but will not overflow the mold body.
5. The method for preparing a food-grade layered hydrogel according to claim 1, characterized in that: In step 4, liquid nitrogen is poured in to cover 2 / 3 of the copper column.
6. The method for preparing a food-grade layered hydrogel according to claim 1, characterized in that: In step 5, thaw at room temperature for 2 hours until the gel is thawed.
Citation Information
Patent Citations
Preparation method of food-grade hydrogel with multistage layered structure
CN115969031A
Bidirectional freeze casting for fabricating lamellar structures
US20170100857A1